Assignment of O–O and Mo=O Stretching Frequencies of Molybdenum/Tungsten Complexes Revisited - Choon Wee Kee (Journal of Chemistry)
The assignment of peroxo stretching frequencies for Molybdenum and Tungsten complexes is studied by DFT and MP2 calculations. We found that M06 functional is unsuitable for assignment of Mo=O and O–O stretches in CpMo(η2-O2)OCH3 and we found that MP2 and even the def2-TZVP do not give accurate order of asymmetric and symmetric Mo=O stretching. We recommend the M06L, which is a good compromise between speed and accuracy, for works involving these complexes. For a series of ten Molybdenum and Tungsten complexes studied we found that, for Mo/W=O stretching frequencies at M06L/def2-TZVP, after scaling, a small RMSD of 15 cm−1 could be obtained. However peroxo stretching frequencies RMSD remains high at 40 cm−1 after scaling. This could potentially point out the need for reassignment of experimental peroxo frequencies in some of the works cited in this report.